Gender-Specific Variation in the Prognosis of Papillary Thyroid Cancer TNM Stages II to IV. (6th December 2012) - Hsieh, Sheng-Hwu; Chen, Szu-Tah; Hsueh, Chuen; Chao, Tzu-Chieh; Lin, Jen-Der
Abstract : To investigate the correlation between gender and the clinical presentation of papillary thyroid cancer and the long-term followup results, 435 patients who underwent total or near-total thyroidectomy were enrolled in this study. Among these papillary thyroid cancer patients, 12.2% showed lymph node metastases and a higher incidence of male patients in the N1b group. There were 65 from 316 female (20.6%) and 49 from 120 male (40.8%) patients who had a postoperative disease progression. A total of 55 (12.6%) patients died of thyroid cancer. Male patients showed a higher thyroid cancer mortality than the females. Multiple regression analysis showed that male gender was an independent risk factor for cancer recurrence and mortality. Male patients with TNM stages II to IV of papillary thyroid cancer need to adopt aggressive surgical and postoperative 131 I therapy.